2016
DOI: 10.1002/ange.201605271
|View full text |Cite
|
Sign up to set email alerts
|

Vinylboronic Acids as Fast Reacting, Synthetically Accessible, and Stable Bioorthogonal Reactants in the Carboni–Lindsey Reaction

Abstract: Bioorthogonal reactions are widely used for the chemical modification of biomolecules.T he application of vinylboronic acids (VBAs) as non-strained, synthetically accessible and water-soluble reaction partners in ab ioorthogonal inverse electron-demand Diels-Alder (iEDDA) reaction with 3,6-dipyridyl-s-tetrazines is described. Depending on the substituents,VBA derivatives give second-order rate constants up to 27 m À1 s À1 in aqueous environments at room temperature, which is suitable for biological labeling ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…This level of reactivity is unprecedented for an unstrained dienophile. This is ≈1000 fold higher than the recently reported vinylboronic acid dienophile, 17 and ≈ 20 fold higher than strained alkyne bicyclo[6.1.0]non-4-yne (Figure 3f). 23 After optimizing the reaction parameters, the reaction between OBF3 and dPy-Tz was complete within 15 min to give IEDDA cycloaddition product in 96% yield (Figure 3g).…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…This level of reactivity is unprecedented for an unstrained dienophile. This is ≈1000 fold higher than the recently reported vinylboronic acid dienophile, 17 and ≈ 20 fold higher than strained alkyne bicyclo[6.1.0]non-4-yne (Figure 3f). 23 After optimizing the reaction parameters, the reaction between OBF3 and dPy-Tz was complete within 15 min to give IEDDA cycloaddition product in 96% yield (Figure 3g).…”
Section: Resultscontrasting
confidence: 51%
“…[11][12][13][14] The recently reported vinylboronic acid dienophile, unlike the abovementioned unstrained alkenes, has satisfactory kinetics (k2 = 27 M -1 s -1 ), is easily synthesized, and is relatively stable (Figure 1c). [15][16][17] Development of new unstrained dienophiles is still of interest, particularly if improvements in reaction kinetics with tetrazines can be obtained and achieve rates identical to those observed for strained dienophiles. Furthermore, the use of chemical triggers for temporal controllable initiation of the reaction remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Ideally, one would like to use linker chemistry that tethers the active drug to the targeting molecule in a stable fashion, and allow for selective cleavage at the desired site of action. 20 , 26 , 27 , 28 , 29 Through the use of click chemistry and the concept of co-localization, 30 , 31 the linker can be very stable until enrichment-triggered release (ETR). The applicability of the approach is not limited to cell surface as in the case of antibody-mediated delivery (or ADC) because of the use of small molecules for both targeting and cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…65 In recent years, additional orthogonal reactions have been reported that promise to bolster multi-parameter imaging and other applications. 18,62,6669…”
Section: Thinking Outside the (Tool)boxmentioning
confidence: 99%